Relative acceleration as a new indicator of game intensity in soccer - Sonderegger, K.; Rumo, M.; Tschopp, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Intensity in team sports has been commonly measured on the basis of distances covered in different speed zones. It was recently noted that the problem with this approach is that short acceleration does not contribute to game intensity because the required speed is not achieved. Relative acceleration accounts for these short-term actions and may be therefore a more valid indicator of game intensity. Methods: During 14 official games, 90 positional datasets were collected from 69 elite junior players (mean age, 17.0 ± 0.6 y) of the highest and 91 datasets from 69 sub-elite junior players (mean age, 17.9 ± 0.9 y) of the second highest national U18 championship levels, using the Local Position Measurement System. Based on the raw acceleration and speed data, each acceleration peak was identified as a single action. For each action, the relative acceleration was calculated as a ratio between the acceleration of the action and the maximum possible acceleration, dependent of the initial running speed, which was determined in a sprint test conducted prior to the games. All actions were classified into four intensities based on the relative acceleration and the initial running speed. The number of high-, moderate-, low-, and very low-intensity actions were then compared with commonly used speed zones (high-speed running [HSR] > 19.8 km/h and sprinting [S] > 25 km/h). Differences between the two performance levels were determined by calculating the effect sizes (ES). Results: Elite junior players had more of high- (84 vs 66), moderate- (90 vs 82), and low- (183 vs 176) intensity actions. The difference is larger in high- (ES, 0.91) than in moderate- (0.48) and low- (0.28) intensity actions. The number of high-intensity actions yields a larger ES than the commonly used indicators of game intensity such as distances covered in high-speed zones (HSR: 522 vs 431 m; ES, 0.50; S: 111 vs 76 m; ES, 0.51). Comparison between the elite and sub-elite players for specific positions yielded a larger ES when number of high-intensity actions rather than common speed zones were used, except for fullbacks (central midfield: ES of 1.38 vs 0.52 [HSR]/0.09 [S]; centre back: ES of 0.68 vs 0.48/0.31; forward: ES of 1.47 vs 0.52/-0.03; wide midfield: 0.64 vs -0.89/0.28; fullbacks: ES of 0.87 vs 1.22/1.88). Discussion and Conclusion: The differences in game intensity between elite and sub-elite junior soccer players is larger when expressed by number of high-intensity actions calculated with relative acceleration than by commonly used speed zones. The difference can be explained by the fact that using relative acceleration to determine intensity results in taking high accelerations from low initial running speeds as well as lower accelerations from high initial speeds into account. Therefore, the new indicator proposed here removes the bias introduced by the commonly used speed zones. ABSTRACT FROM AUTHOR